ANALYSIS OF ELECTRONIC PAYROLL INFORMATION SYSTEM REQUIREMENTS FOR NON-CIVIL SERVANT EMPLOYEES AT UNIVERSITAS NEGERI SURABAYA - Anggraini, Ira Diana; Sujarwanto; Riyanto, Yatim; Roesminingsih, Erny; Amalia, Kaniati (STKIP Citra Bakti, 2026)
The digital transformation of financial governance in higher education institutions has encouraged universities to improve accountability, transparency, and efficiency in payroll administration systems. However, payroll management for non-civil servant employees at Universitas Negeri Surabaya is still highly dependent on manual administration and spreadsheet-based processing, resulting in administrative inefficiencies, delays in payroll processing, fragmented data management, and a high risk of human error. Therefore, this study aimed to analyze the requirements for developing an Electronic Payroll Information System (SIGAJI) for non-civil servant employees at Universitas Negeri Surabaya. This study employed a descriptive qualitative approach focusing on system requirements analysis. The research was conducted at Universitas Negeri Surabaya, particularly within units related to payroll administration and financial management for non-civil servant employees. Data were collected through observation, documentation, and literature review. The data sources included payroll administration documents, payroll recapitulation reports, salary slips, personnel data records, payroll workflow documents, institutional regulations, and related literature concerning payroll information systems and digital financial governance. The collected data were analyzed using qualitative descriptive analysis techniques through data reduction, data organization, requirement identification, and classification of functional and non-functional system requirements. The findings indicated that the existing payroll management system had not yet supported integrated and electronic-based payroll administration. Payroll activities were still conducted separately and manually, causing repetitive data entry, payroll processing delays, data inconsistencies, and difficulties in payroll monitoring and reporting. The study also identified organizational and regulatory requirements emphasizing the need for an integrated payroll information system aligned with institutional policies and digital governance principles. Functional requirements identified in this study included employee data management, payroll calculation, payroll reporting, payroll history management, and digital payslip services. Meanwhile, non-functional requirements included system security, accessibility, usability, operational efficiency, integration capability, and role-based access control. The study concluded that the development of an integrated electronic payroll information system is necessary to improve payroll administration efficiency, reduce administrative errors, strengthen transparency, and support accountable financial governance at Universitas Negeri Surabaya. The findings of this study may serve as the basis for further system design and prototype development of SIGAJI.